2020
DOI: 10.1186/s12882-020-02151-7
|View full text |Cite|
|
Sign up to set email alerts
|

The impact of hypertension on chronic kidney disease and end-stage renal disease is greater in men than women: a systematic review and meta-analysis

Abstract: Background Hypertension (HTN) is an established risk factor for chronic kidney disease (CKD) and end-stage renal disease (ESRD). Whether sex differences in the effect of HTN on CKD and ESRD incidence exist remains unclear. This systematic review and meta-analysis was conducted to evaluate the relative impact of HTN on CKD and ESRD risk in women compared with men. Methods We systematically searched Embase and PubMed for cohort studies until 24 July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 47 publications
4
43
3
3
Order By: Relevance
“…We also demonstrated that RBE exhibits a higher antioxidant capacity than resveratrol itself [ 17 ]. Given that RBE has been shown to produce highly beneficial biological effects [ 18 ], the aim of the current study was: to (1) evaluate the effectiveness of RBE at low and high doses vs. resveratrol in the treatment of hypertension in a model of pediatric CKD; and (2) elucidate the mechanisms related to the beneficial effects, with a focus on the gut-kidney axis.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that RBE exhibits a higher antioxidant capacity than resveratrol itself [ 17 ]. Given that RBE has been shown to produce highly beneficial biological effects [ 18 ], the aim of the current study was: to (1) evaluate the effectiveness of RBE at low and high doses vs. resveratrol in the treatment of hypertension in a model of pediatric CKD; and (2) elucidate the mechanisms related to the beneficial effects, with a focus on the gut-kidney axis.…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors informed us that there are some errors due to a typesetting mistake. The corrections are as follows: Figure 1 has been updated as the arrows in the figure were distorted during the production process.…”
mentioning
confidence: 99%
“…This disparity is unlikely to be explained by biological differences alone. 44 We speculate that male subjects have significantly worse lifestyles in the present study, and the prevalence of underlying diseases is also significantly higher, such as hypertension, dyslipidemia, and obesity. The above factors may be related to the significantly lower baseline eGFR in men, and the significant discrepancies in the abovementioned baseline indicators might also contribute to the sex difference of the present results.…”
Section: Discussionmentioning
confidence: 56%